Serial Assessment of Immune Status by Circulating CD8+ Effector T Cell Frequencies for Posttransplant Infectious Complications - Shinji Uemoto; Kazue Ozawa; Hiroto Egawa; Yasutsugu Takada; Hiroshi Sato; Satoshi Teramukai; Mureo Kasahara; Kohei Ogawa; Masako Ono; Kenji Takai; Masanori Fukushima; Kayo Inaba; et al. (Clinical and Developmental Immunology)
To clarify the role of CD8+ effector T cells for infectious complications, 92 recipients were classified according to the hierarchical clustering of preoperative CD8+CD45 isoforms: Group I was naive, Group II was effector memory, and Group III was effector (E) T cell-dominant. The posttransplant infection rates progressively increased from 29% in Group I to 64.3% in Group III recipients. The posttransplant immune status was compared with the pretransplant status, based on the measure (% difference) and its graphical form (scatter plot). In Groups I and II, both approaches showed a strong upward deviation from pretransplant status upon posttransplant infection, indicating an enhanced clearance of pathogens. In Group III, in contrast, both approaches showed a clear downward deviation from preoperative status, indicating deficient cytotoxicity. The % E difference and scatter plot can be used as a useful indicator of a posttransplant infectious complication.